Contributing factors of fatigue in patients with type 2 diabetes: A systematic review. (August 2021) - Bi, Yaxin; Zhang, Lu; Li, Xiangning; Kan, Yinshi; Li, Shuang; Zou, Yan; Liu, Lin; Yuan, Yuan; Gong, Weijuan; Zhang, Yu
Abstract: Remarkable evidence supports the link between type 2 diabetes (T2DM) and fatigue. However, a unifying recommendation to identify and prevent fatigue or to prevent its clinical consequences in T2DM is not available at present. Therefore, this study aimed to conduct a systematic review to summarize the definition, measurement tools, and contributing factors of fatigue in T2DM. Nine articles were included for analysis, and results showed that T2DM fatigue was associated with five major factors, including sociodemographic factors, clinical disease factors, inflammatory factors, psychological factors, and behavior and lifestyle. The contributing factors of T2DM fatigue are reviewed, and clinical benefits provide a theoretical basis for further clinical intervention to prevent the occurrence of fatigue and improve the patient's treatment compliance and self-management ability and may be beneficial to their quality of life. Highlights: Focus on the relationship between T2DM and fatigue symptom. Summarize the definition, measurement tools, and contributing factors of T2DM fatigue. T2DM fatigue is influenced by demography, disease, Inflammation, psychology, lifestyle. This systematic review provides a foundation for developing intervention in T2DM fatigue.